The Potential of Artificial Intelligence in Creating Contemporary Paintings Inspired by Saudi Najdi Heritage (Al-Academy, 2025)
Amid the rapid technological advancements, artificial intelligence has emerged as one of the most prominent tools of the modern era, contributing to the expansion of artistic creativity. It has become an active partner in generating ideas and shaping aesthetic visions, while enabling artists to explore new methods and forms that transcend the limits of traditional tools.This research seeks to explore the role of artificial intelligence technologies in developing creativity among contemporary visual artists while preserving the visual identity inspired by Najdi Saudi heritage. The study aims to identify the most significant uses of artificial intelligence in producing artworks, to reveal sources of inspiration from Najdi heritage, and to apply AI tools to paintings inspired by this heritage in order to create contemporary creative works.The research adopts the descriptive-analytical method, with a sample consisting of five artworks produced by the researcher. The theoretical framework is structured around two main axes: applications of artificial intelligence in visual arts, and visual sources of inspiration from Najdi Saudi heritage.The study concludes with several key findings, most notably: the diversity of AI applications in art, including text-to-image generation and style transfer; Najdi architecture, with its ornamental and chromatic elements, provides a rich source of visual inspiration; and AI-based processing of traditional ornamental elements has offered new interpretations without erasing their original identity. The artworks maintained their fundamental visual structure despite formal transformations, confirming the possibility of integrating artificial intelligence into contemporary art while preserving cultural heritage.